Breaking Barriers via Refugees: Cultural Transmission and Women's Economic Empowerment - Mevlude Akbulut-Yuksel; Abdurrahman B. Aydemir; Murat Güray Kirdar; Belgi Turan (Institute of Labor Economics (IZA), 2025)
This paper examines the horizontal transmission of gender norms using the forced migration of ethnic Turks from Bulgaria to Türkiye after the fall of the Iron Curtain as a natural experiment. Despite shared linguistic and religious ties, migrant women held more progressive gender norms and stronger labor market attachment than native Turkish women. Their arrival increased labor market participation among native women, particularly in male-dominated manufacturing, while men's outcomes remained unchanged. Additionally, native women's fertility declined, and middle school attainment rose, aligning with refugee women's patterns. Exposure to progressive norms reshaped native women's roles in work and family life.
Keywords: J16; J15; J13; N45; 330; culture; horizontal transmission; social learning; migration